Digital Volume Pulse Analysis to Differentiate Diabetic From Non-Diabetic Subjects - Qawqzeh, Yousef (Communications in Mathematics and Applications, 2019)
This paper aims to examine the validity of digital volume pulse waveform index namely the diastolic pulse peak (Dpp) in the evaluation of type II diabetics. In total, 153 participants (115 healthy participants and 48 diabetics type II patients) are recruited during the study. A customized algorithm for DVP waveform analysis is developed in MATLAB to analyze and calculate Dpp and b/a indices. The b/a index is found to be negatively correlated with both age and HbA1C test (\(r=-83.8\) and \(r=-66.7\), respectively), while Dpp index is found to be positively correlated with age and HbA1C test (\(r=65.7\) and \(r= 63.3\), respectively). The DVP's Dpp index showed strong association with age and HbA1C test since it remains statistically significant based on the analysis of multi-linear regression. The model revealed that b/a, age, and Dpp contribute by 71.9% of the variance in HbA1C test. The findings showed that age, b/a, and Dpp indices are promising factors in diabetes type II assessment. These findings expand the potential utility of DVP signal in clinical settings.